P-wave velocity of discrete samples (DPW) from IODP Hole 389-M0098A - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
P-wave velocity data from discrete samples from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). Discrete samples for P-wave velocity measurements were taken during the onshore phase of expedition 389, which took place between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. The measurements were performed on cylindrical core plugs drilled approx. every 1.5 meter perpendicular to the split surface of the working halves of the core sections. P-wave velocity was measured first wet straight after the initial sampling, again after the samples have been dried in a convection oven and a third time after being resaturated with tap water. All measurements were performed with a Geotek PWL-D velocimeter for discrete P-wave measurements. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025